Caribbean mangrove forests act as coral refugia by reducing light stress and increasing coral richness. Issue 3 (15th March 2021) - Stewart, Heather A.; Kline, David I.; Chapman, Lauren J.; Altieri, Andrew H.
Abstract: Foundation species structure communities by creating habitat and modifying environmental conditions, and there is increasing interest in how foundation species, such as corals and mangroves, interact with one another as these interactions can have cascading effects on diversity and abundance of associated organisms. Given recent reports of corals living on or between mangrove roots under the canopy, we hypothesized that mangroves can serve as a refuge for corals from stresses such as high solar irradiance and temperatures that are associated with the adjacent shallow reef. Using field surveys and a reciprocal transplant experiment, we tested the effects of light and habitat (e.g., reef or mangrove) on coral community structure (i.e., coral species richness, abundance, and diversity) and condition (i.e., level of bleaching, tissue loss, and mortality). The surveys revealed higher coral richness in mangroves than on the adjacent reef, indicating that mangroves can serve as refugia for numerous coral species. Our experimental manipulation of light in mangrove and reef habitats indicated that light intensity is a key environmental parameter mediating coral bleaching and survival, with mangrove habitats providing a refuge from the light stress experienced on nearby shallow reefs. Moreover, our experiment revealed that reef corals bleached less than mangrove corals following transplantation, regardless of whether they were transplanted into mangrove or reef habitats. We suggest that the lower coral richness of the shallow reef is the result of the extreme environmental conditions that select for a subset of coral species able to tolerate these conditions. The facilitative interactions that allow mangroves to act as coral refugia by reducing environmental stress will likely become increasingly important with global climate change.